Observations on the structure of the Early Permian reptile Stereosternum tumidum Cope - Modesto, Sean Patrick (Bernard Price Institute for Palaeontological Research, 1999)
New information on the mesosaur Stereosternum tumidum is derived from a nearly complete skeleton and other material. Two autapomorphies are identified for Stereosternum: (1) presence of an ‘odontoid’ axial process, formed probably by co-ossification of the atlantal pleurocentrum to that of the axis, and (2) the presence of a posterior supraneural process on the neural arch of dorsal vertebrae. Temporal fenestration appears to be absent in Stereosternum, marginal teeth are determined to be subcircular rather than oval in cross section and in this respect resemble those of Mesosaurus, and there is no sign of fracture planes in the caudal vertebrae that could be indicative of caudal autotomy. A phylogenetic analysis, based on a slightly modified data matrix from the literature, identifies Mesosauridae as the sister group of Parareptilia within the reptilian clade Anapsida (sensu lato). As a consequence of this rearrangement of amniote tree topology, the stem-based taxon Sauropsida is regarded to be in abeyance, because it now includes exactly the same taxa as Reptilia. Mesosaurs, at more than 275 million years of age, can be recognised as the oldest known anapsid reptiles.
Keywords: stereosternum; mesosaurs; Anapsida; phylogeny; permian